2001
DOI: 10.1507/endocrj.48.509
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Changes in Circulating Leptin Levels in Women Undergoing Total Abdominal Hysterectomy.

Abstract: Abstract.To investigate the effects of total abdominal hysterectomy on circulating leptin levels, 16 pre-and 8 postmenopausal patients with uterine leiomyoma or carcinoma in situ of the uterine cervix were enrolled. Serum levels of leptin and fasting blood sugar (FBS) were determined before (day -7) and after surgery (day +1 and +7). Body mass index (BMI) was recorded at day -7 and +7. Anesthesia duration, surgical duration, hematology, and blood loss during surgery were recorded. Relations of these variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…One study showed that serum leptin concentrations were gradually decreased from 16 h after operation in patients who underwent surgery due to trauma or large bowel diseases [30]. Similar results were also observed in a study in women who underwent total abdominal hysterectomy [31]. In veterinary medicine, a study reported changes in leptin concentrations before and after treatment in dogs with naturally occurring pituitary-dependent hyperadrenocorticism.…”
Section: Discussionsupporting
confidence: 53%
“…One study showed that serum leptin concentrations were gradually decreased from 16 h after operation in patients who underwent surgery due to trauma or large bowel diseases [30]. Similar results were also observed in a study in women who underwent total abdominal hysterectomy [31]. In veterinary medicine, a study reported changes in leptin concentrations before and after treatment in dogs with naturally occurring pituitary-dependent hyperadrenocorticism.…”
Section: Discussionsupporting
confidence: 53%
“…In our study, leptin increased 24 hours after surgery as in this study and IL-6 also increased postoperatively, but neither they nor we found any correlation between leptin and IL-6. The increase of leptin 24 hours after surgery is similar to observations reported by previous studies [ 6 , 7 , 12 , 17 ].…”
Section: Discussionsupporting
confidence: 91%
“…Leptin (OB protein), is the adipocyte-derived product of antiobesity gene and its circulating concentrations indirectly reflect body fat stores. Serum cytokines may upregulate leptin levels [ 3 , 5 , 6 ]. Leptin is structurally similar to the granulocyte colony-stimulating factor (G-CSF) from IL-6 cytokine family [ 3 ].…”
Section: Introductionmentioning
confidence: 99%